Cardiac Stem Cell Therapy: An Overview (Cardiovascular Journal, 2010)
Cardiovascular diseases are the major causes of mortality and morbidity throughout the world. Treatment of these diseases is often incomplete, suboptimal and far from permanent cure. One of the reasons behind this is the nature of heart as a terminally differentiated organ. Preclinical and clinical research in the last few decades has put a challenge to this conventional belief regarding the inability of regeneration of the cardiomyocytes. Embryonic, foetal and a wide range of adult stem cells have been used so far. Differentiation of adult somatic cells has lead to breakthrough discovery of induced pleuripotent stem cells which may be a potential solution of controversy over embryonic stem cell issue. Stem cells specially those of bone marrow origin are already being used in a limited scale to treat acute myocardial infarction, chronic myocardial ischaemia and cardiomyopathy with efficacy, feasibility and safety. Mesenchymal stem cells and adult cardiac stem cells are on the way to bedside use. skeletal myoblasts have been associated with life-threatening ventricular arrhythmia. Stem cells combined with tissue engineering have produced prosthetic tissue valves, and hope for manufacturing whole heart ex vivo in near future. However, like other rapidly evolving modalities, there are more questions than answers. Exact indications, patient selection, cell selection, timing of therapy, efficacy of repeated therapies, co-administration of growth factors, and genetic modification of stem cells are yet to be determined with precision. International community is coming forward with enthusiasm and vigor to explore the enormous potential of stem cell therapy and regenerative medicine. Future research will hopefully facilitate more versatile application of stem cells in treating the life-threatening and disabling ailments of mankind. Keywords: Stem cell; regenerative medicine DOI: 10.3329/cardio.v3i1.6429Cardiovasc. j. 2010; 3(1): 66-80